A Review on Property Reforms for Fiber Matrix Composites through Various Surface Treatment of Fibers. (February 2020) - Basak, Reshmi; Gohil, Piyush P.; Dey, Sudip; Pandey, Krishna Murari
Abstract: The primary factor that defines the final performance of any composite material is the fiber-matrix interface. Hence, efficient amount of adhesion is needed for full-fledged performance of composite materials. When fibers are used without surface modification, they tend to produce composites with low strength. This in turn leads to weak adhesion and poor bonding between the fiber and matrix. Hence, there is a massive apprehension to alter the surface of fibers through various procedures, in order to overcome their intrinsic downsides and effectively employ these materials in countless applications. This paper deals with a review of prevailing research studies fixated on the surface treatment of fibers.